Ethical and legal issues in neurology - Beresford, H. Richard, 1930; Bernat, James L (Elsevier, 2013)
"Advances in our understanding of the brain and rapid advances in the medical practice of neurology are creating questions and concerns from an ethical and legal perspective. Ethical and legal issues in neurology provides a detailed review of various general aspects of neuroethics, and contains chapters dealing with a vast array of specific issues such as the role of religion, the ethics of invasive neuroscience research, and the impact of potential misconduct in neurologic practice. The book focuses particular attention on problems related to palliative care, euthanasia, dementia, and neurogenetic disorders, and concludes with examinations of consciousness, personal identity, and the definition of death"-- Publisher's description
Keywords: Forensic neurology; Neurology -- Moral and ethical aspects; Neurologie -- Législation; Neurology -- ethics; Neurology -- legislation & jurisprudence; Neurologie -- éthique; Neurologie -- législation et jurisprudence